The Efficacy of Topical Formulation Containing Ciplukan (Physalis angulata Linn.) in Modulating Interleukin-17 and Interferon Gamma Expression in Mice (Mus musculus) Psoriasis Model - Suwarsa O; Dharmadji HP; Rohmawaty E; Mareta S; Gunawan H; Dwiyana RF; Achdiat PA; Sutedja E; Pangastuti M (Dove Medical Press, 2023)
Oki Suwarsa,1 Hartati Purbo Dharmadji,1 Enny Rohmawaty,2 Shela Mareta,1 Hendra Gunawan,1 Reiva Farah Dwiyana,1 Pati Aji Achdiat,1 Endang Sutedja,1 Miranti Pangastuti1 1Department of Dermatology and Venereology, Faculty of Medicine, Universitas Padjadjaran-Dr. Hasan Sadikin Hospital, Bandung, West Java, Indonesia; 2Department of Biomedical Science, Faculty of Medicine, Universitas Padjadjaran, Bandung, West Java, IndonesiaCorrespondence: Oki Suwarsa, Department of Dermatology and Venereology, Faculty of Medicine, Universitas Padjadjaran - Dr. Hasan Sadikin Hospital, Jl. Pasteur 38, Bandung, West Java, 40161, Indonesia, Tel +62 813 2275 0101, Email oki.suwarsa@unpad.ac.idBackground: Interleukin 17 (IL-17) and interferon gamma (IFN-γ) play a role in the pathogenesis of psoriasis vulgaris (PV). Topical corticosteroids are still utilised as first-line therapy for mild to moderate PV. However, long-term use of corticosteroid is associated with various side effects. Physalis angulata Linn. (Ciplukan) possesses anti-inflammatory properties that could serve as a potential alternative topical therapy for PV.Objective: To assess the efficacy of topical ciplukan as an anti-inflammatory agent targeting the expression of IL-17 and IFN-γ.Methods: Psoriasis was induced using imiquimod cream, therefore divided into five groups. Group I, the psoriasis control group, received only imiquimod cream. Groups C1 and C2 received imiquimod cream followed by a mixture of Ciplukan and vaseline in a 1:2 and 1:4 ratio, respectively. Group M, the standard therapy group, received imiquimod cream, followed by mometasone furoate cream. Lastly, group V, the vehicle group, received imiquimod cream followed by vaseline album. Expression of IL-17 and IFN-γ in mice's skin tissue was analysed using reverse transcription polymerase chain reaction (RT-PCR) after seven days of treatment.Results: The mean expression of IL-17 in Group C1 (22.60) was significantly lower (p = 0.012) than in the psoriasis control group (23.60), and there was no significant difference (p = 0.613) in Group M (22.41). The mean expression of IFN-γ in Group C1 (26.97) and Group C2 (27.03) was also significantly lower (p = 0.026 and p = 0.026, respectively) than Group I (28.80), and there was no significant difference (p = 0.180 and p = 0.093, respectively) than Group M (26.03).Conclusion: Expression of IL-17 and IFN-γ in the ciplukan group is lower than in the psoriasis control group, and there is no significant difference compared to the standard therapy group.Keywords: IFN-γ, IL-17, Physalis angulata Linn, psoriasis vulgaris